Respuesta :
given,
9(x+1) = 25 + x
expanding,
9x + 1 = 25 + x
bringing x to left hand side and taking 1 to right hand side with change in their respective signs,
9x - x = 25-1
=> 8x = 24
transposing 8 ,
=> x = 24/8 = 3
Hence x = 3
9(x+1) = 25 + x
expanding,
9x + 1 = 25 + x
bringing x to left hand side and taking 1 to right hand side with change in their respective signs,
9x - x = 25-1
=> 8x = 24
transposing 8 ,
=> x = 24/8 = 3
Hence x = 3
Answer:
Option [A]
Step-by-step explanation:
Hi student! Let me help you out on this question.
_______________
First of all we need to use the distributive property and multiply 9 times x and 1.
[tex]\boldsymbol{9(x+1)=9\cdot x+9\cdot1=9x+9}[/tex]
[tex]\boldsymbol{9x+9=25+x}[/tex]
Subtract x from both sides
[tex]\boldsymbol{8x+9=25}[/tex]
Subtract 9 from both sides
[tex]\boldsymbol{8x=16}[/tex]
Next, divide both sides by 8
[tex]\boldsymbol{x=2}[/tex]
Hope that this helped! Best wishes.
[tex]\star\boldsymbol{Reach\:far.\:Aim\:high.\:Dream\:big.}[/tex]
-Greetings!-
_______________